2010
DOI: 10.1007/s11104-010-0465-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of grassland vegetation cover in a catchment in Inner Mongolia, China, derived from MODIS data products

Abstract: Conditions, distribution and development of vegetation in semi arid regions are highly variable. In this study we detected the temporal and spatial variability of vegetation in the Xilin river catchment from 2000 to 2008 by analysis of Moderate Resolution Imaging Spectroradiometer (MODIS) data products of that period. The study is based on LAI (Leaf area index) and supported by NDVI (Normalized difference vegetation index) and LST (Land surface temperature) data with a spatial resolution of 1 km. The mean LAI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The MODIS LAI data were also used to model P for each pixel. Schaffrath et al (2010) found a linear relationship between precipitation and mean LAI for the vegetation period in the Xilin river catchment (R 2 = 0.78). We used this relationship to estimate P from the mean LAI (doy 113 to doy 297) of each pixel (Fig.…”
Section: Generation Of Input Data From Terra Modismentioning
confidence: 91%
See 2 more Smart Citations
“…The MODIS LAI data were also used to model P for each pixel. Schaffrath et al (2010) found a linear relationship between precipitation and mean LAI for the vegetation period in the Xilin river catchment (R 2 = 0.78). We used this relationship to estimate P from the mean LAI (doy 113 to doy 297) of each pixel (Fig.…”
Section: Generation Of Input Data From Terra Modismentioning
confidence: 91%
“…Additionally, several micrometeorological towers collected data (cp. Ketzer et al 2008;Wang et al 2009);Schaffrath et al (2010) analysed the spatiotemporal variability of precipitation and vegetation in this particular area using MODIS data. They found the conditions in the study area generally represent the steppe of the catchment, and the course of LAI is driven by precipitation, which had an annual mean of 210 mm with a high coefficient of variation (36%) from 2000 to 2008.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely a function of geomorphological properties such as aspect, slope and soil type, but also due to the large variability of convective rainfall events across the study area (e.g. Schaffrath et al, 2011). Following superimposition of the footprints over the land cover data, the spatial contributions of different surface properties to each flux observation can be quantified (Fig.…”
Section: Land Covermentioning
confidence: 99%
“…Besides Tibet, Inner Mongolia is China's most important province for grassland-based livestock production, and desertification due to overgrazing is a major problem for extensive areas (Meurer and Jiang, 2001). In addition, the land cover in the investigation area varies distinctly in space and time (Ketzer et al, 2008;Schaffrath et al, 2011). We postulate that airborne EC flux measurement is a promising tool to gain new insights into the spatial variability of heat and moisture exchange across the XRC.…”
Section: Introductionmentioning
confidence: 99%